Cell Therapy in Chagas Disease - Antonio C. Campos de Carvalho; Regina C. S. Goldenberg; Linda A. Jelicks; Milena B. P. Soares; Ricardo Ribeiro dos Santos; David C. Spray; Herbert B. Tanowitz (Interdisciplinary Perspectives on Infectious Diseases)
Chagas disease which is caused by the parasite Trypanosoma cruzi is an important cause of cardiomyopathy in Latin America. In later stages chagasic cardiomyopathy is associated with congestive heart failure which is often refractory to medical therapy. In these individuals heart transplantation has been attempted. However, this procedure is fraught with many problems attributable to the surgery and the postsurgical administration of immunosuppressive drugs. Studies in mice suggest that the transplantation of bone-marrow-derived cells ameliorates the inflammation and fibrosis in the heart associated with this infection. Cardiac magnetic resonance imaging reveals that bone marrow transplantation ameliorates the infection induced right ventricular enlargement. On the basis of these animal studies the safety of autologous bone marrow transplantation has been assessed in patients with chagasic end-stage heart disease. The initial results are encouraging and more studies need to be performed.